B2B or B2C?: Dutch approaches towards marketing and the consumer, 1945-1968, with particular attention to Heineken's Brewery - Sluyterman, K.E. (Koninklijk Nederlands Historisch Genootschap, 2017)
In this article I analyse how Dutch companies approached the consumers and marketing during the years 1945-1968, a period during which the Netherlands became a ‘consumer society’. In the first part I examine articles in the Dutch journal Tijdschrift voor Efficiëntie en Documentatie (ted, or Journal for Efficiency and Documentation), a leading management periodical. This examination shows how new ideas from abroad were taken up and disseminated in the Netherlands by both management consultants and large producers of consumer goods such as Unilever and Philips. In the second part of this article I take a closer look at Heineken’s brewery, drawing on the company’s archives. Heineken closely followed the ideas afloat at the time and put them into practice. However, the Heineken case also shows the different approaches necessary for business-to-consumer (b2c) and business-to-business (b2b) relationships. The second type of relationships deserves more attention from historians.
Keywords: history; Low Countries; Netherlands; Belgium; consumption history